Pengaruh Pembiayaan Mudharabah Dan Pembiayaan Musyarakah Terhadap Roa Bank Umum Syariah Periode 2016 – 2021 - Syafira Nur Hasanah; Nahruddien Akbar (Prodi Ekonomi Syariah Universitas Majalengka, 2024)
The study was conducted to determine the effect of Mudharabah Financing and Musyarakah Financing on Return on Assets (ROA) in Islamic Banking for the period 2016 to 2021. The type of data in the study is secondary data, with a population of all Islamic banks registered with Bank Indonesia. The sample selection was made by the purposive sampling method. The data analysis technique uses multiple linear regression analysis with SPSS 25. The research showed that between Mudharabah and ROA, there was a partially significant positive effect. As for Musyarakah and ROA, there is a partial negative effect. Furthermore, together, there is a significant influence of Mudharabah and Musyarakah on ROA.